Asymmetries and intensity of integration of The Caribbean - Gutiérrez, Constantina; Álvarez, Stefania S. (Iberoamerican Journal of Development Studies, 2016)
The intensification of integration processes is political and economically desirable for developing countries. However, the existence of asymmetries in the income level hinders the realization of that goal. These latter issues are extremely important in The Caribbean. The main results are that deeper integration integration is verified de facto accompanying institutional efforts, and that this enhancement was sponsored by the formation of two groups converging internally. Such process is more approximate to the formation of convergence clubs that reducing asymmetry that has been proposed as a goal in the signed agreements.
Keywords: de facto integration; de iure integration; asymmetries; The Caribbean; Caricom; convergence clubs